2011
DOI: 10.1002/cbf.1842
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of silibinin induces cell‐cycle arrest and apoptosis on HeLa cells

Abstract: Silibinin, an effective anti-cancer and chemopreventive agent in various epithelial cancer models, has been reported to inhibit cancer cell growth through mitogenic signalling pathways including cervical cancer. However, the underlying mechanisms are still not well elucidated. Here, we assessed the effect of silibinin on human cervical carcinoma cell cycle modulation, apoptosis induction and associated molecular alterations by employing HeLa cell line. Silibinin treatment of HeLa cells resulted in a G2 arrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Moreover, other studies have also demonstrated that the anti-cancer mechanism of some agents was associated with cell cycle arrest and apoptosis induction. 16) Further, recent study have suggested that cell cycle destruction by exogenous agent was more promising effect rather than its apoptotic potential. 17) Furthermore, growing body of evidence provides evidence that morphine could inhibit various type of cancer cell growth, which were mostly regulated through inhibition of angiogenesis, 18) promoting apoptotic death via c-Jun N-terminal kinase (JNK)/caspase pathway 19) and modulating vascular endothelial growth factor (VEGF)-A expression, 20) which all leads to control tumor micro environment and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have also demonstrated that the anti-cancer mechanism of some agents was associated with cell cycle arrest and apoptosis induction. 16) Further, recent study have suggested that cell cycle destruction by exogenous agent was more promising effect rather than its apoptotic potential. 17) Furthermore, growing body of evidence provides evidence that morphine could inhibit various type of cancer cell growth, which were mostly regulated through inhibition of angiogenesis, 18) promoting apoptotic death via c-Jun N-terminal kinase (JNK)/caspase pathway 19) and modulating vascular endothelial growth factor (VEGF)-A expression, 20) which all leads to control tumor micro environment and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin exhibits anti-cancer activities mainly due to the cell cycle arrest [330,[338][339][340][341]. It induces G1 phase arrest in human pancreatic cancer SW1990 and AsPC-1, and breast cancer MCF-7 and MCF-10A cells [330,339,340], whilst it causes G2 phase arrest in human cervical cancer HeLa, and gastric cancer MGC-803 and SGC-7901 cells [338,341]. It also decreases the expressions of CDKs such as CDK1, CDK2, CDK4 and CDK6 that are involved in G1 and G2 progression [338,339].…”
Section: Silibininmentioning
confidence: 99%
“…It induces G1 phase arrest in human pancreatic cancer SW1990 and AsPC-1, and breast cancer MCF-7 and MCF-10A cells [330,339,340], whilst it causes G2 phase arrest in human cervical cancer HeLa, and gastric cancer MGC-803 and SGC-7901 cells [338,341]. It also decreases the expressions of CDKs such as CDK1, CDK2, CDK4 and CDK6 that are involved in G1 and G2 progression [338,339]. Besides, silibinin suppresses metastasis through ERK1/2 and MMP-9 down-regulation in human thyroid cancer TPC-1, breast cancer MCF-7, renal carcinoma ACHN, OS-RC-2 and SW-839, and epidermoid carcinoma A-431 cells [342][343][344].…”
Section: Silibininmentioning
confidence: 99%
“…Zhang et al [16] In vitro/cervical cancer Result of this study provides a strong rationale for future studies evaluating preventive and/or intervention strategies for silibinin in cervical cancer pre-clinical models Cell arrest in G2 phase, decrease in cyclin-dependent kinases involved in both G1 and G2 progression…”
Section: Cell-cycle Arrest Via Inhibition Of Cyclin-cdk Promoter Actimentioning
confidence: 95%
“…Rather, inhibition of cell cycle regulatory proteins plays a fundamental role in silibinin'smechanism of action, and this may serve as a basis for combined use with conventional chemotherapeutics. [6] The silibinin treatment of HeLa cells was found to arrest cells in G2 arrest and to induce a decrease in CDKs involved in both G1 and G2 progression in a study conducted by Zhang et al [16] In addition, silibinin also showed a dose-dependent and a time-dependent apoptotic death in HeLa cells in both the mitochondrial pathway and the death receptor-mediated pathway, providing a strong rationale for future studies evaluating preventive and/or intervention strategies for silibinin in cervical cancer pre-clinical models.…”
Section: Metabolism and Excretionmentioning
confidence: 98%